Development and evaluation of a quadruple real-time fluorescence-based quantitative reverse transcription polymerase chain reaction assay for detecting Langya, Mojiang, Nipah, and Cedar viruses - Wenjun He; Tian Ma; Yalan Wang; Weifang Han; Jun Liu; Wenwen Lei; Le Zhang; Guizhen Wu (Elsevier, 2024)
The emerging viruses within the genus Henipavirus in the family Paramyxoviridae pose a great threat to public biosafety. To develop a quadruple real-time fluorescence-based quantitative reverse transcription polymerase chain reaction (qRT-PCR) assay is pivotal for the early warning of the potential of zoonotic infectious diseases. Specific primers and probes were designed for the relatively conserved regions based on whole genome sequences of Langya virus (LayV), Mojiang virus (MojV), Nipah virus (NiV), and Cedar virus (CedV), followed by the establishment of a quadruple real-time fluorescence-based qRT-PCR detection method. No cross-reactivity was observed with other viral nucleic acids. The optimal linear detection range for LayV, MojV, NiV, and CedV was 101-108 copies/μL, and the lower limit of detection was 10 copies/μL. Three different DNA concentrations of LayV, MojV, NiV, and CedV (104, 105, and 106 copies/μL) were tested 14 times, achieving good repeatability. The standard deviation of the cycle threshold values for each concentration was <0.5 and the coefficient of variation was <3 %. Furthermore, the amplification efficiency of quadruple real-time fluorescence-based qRT-PCR was >90 %, and the correlation coefficient was >0.99. The established quadruple real-time fluorescence-based qRT-PCR assay for the detection of LayV, MojV, NiV, and CedV exhibits good sensitivity, specificity, and repeatability. Therefore, it can be used to detect Henipavirus and other related clinical specimens.